The Role of Open Lung Biopsy in Critically Ill Patients with Hypoxic Respiratory Failure: A Retrospective Cohort Study - Abdullah Almotairi; Sharmistha Biswas; Jason Shahin (Canadian Respiratory Journal)
Background. The aim of this study was to assess the utility of open lung biopsy in patients with hypoxic respiratory failure of unknown etiology admitted to an ICU and to examine the use of steroid therapy in this patient population. Methods. A retrospective cohort study was performed of all consecutive patients admitted to three tertiary care, university-affiliated, ICUs during the period from January 2000 to January 2012 with the principal diagnosis of hypoxic respiratory failure and who underwent an open lung biopsy. Results. Open lung biopsy resulted in a diagnostic yield of 68% and in a 67% change of management in patients. A multivariable analysis of clinical variables associated with acute hospital mortality demonstrated that postbiopsy systemic steroid therapy (OR 0.24, 95% C.I 0.06–0.96) was significantly associated with improved survival. Complications arising from the biopsy occurred in 30% of patients. Conclusion. Open lung biopsy had significant diagnostic yield and led to major changes in management and aided in end-of-life decision-making in the ICU. Systemic steroid therapy was associated with improved survival. The risk-benefit ratio of open lung biopsy is still unclear, especially given the availability of newer diagnostic tests and possible empirical therapy with steroids.